(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
In the digital economy, accounting plays a very important role in the organization, control and management of material production in the process of managing and distributing the funds of an entity. It is necessary to continuously monitor all processes of an enterprise’s activity. Observing, measuring and recording certain events occurring in the economic activity of an enterprise is a quantitative reflection of its activities. This is the main content of accounting. The purpose of financial accounting is to provide users with complete and reliable financial and accounting information in a timely manner. Any management system needs an appropriate information supply system. Accounting is one of the most important tools for collecting, summarizing and processing information in society.